2017
DOI: 10.4252/wjsc.v9.i2.26
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial function and endoplasmic reticulum stress by nitric oxide in pluripotent stem cells

Abstract: Mitochondrial dysfunction and endoplasmic reticulum stress (ERS) are global processes that are interrelated and regulated by several stress factors. Nitric oxide (NO) is a multifunctional biomolecule with many varieties of physiological and pathological functions, such as the regulation of cytochrome c inhibition and activation of the immune response, ERS and DNA damage; these actions are dose-dependent. It has been reported that in embryonic stem cells, NO has a dual role, controlling differentiation, surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 112 publications
2
11
0
Order By: Relevance
“…The proper function of mitochondria is also crucial for NLRP3 inflammasome activation. Several factors including NO [51] and Ca 2+ [52] can lead to MtD, which may also trigger the NLRP3 inflammasome activation via the release of oxidized mitochondrial DNA (mtDNA) following the engagement of TLRs [21]. MtD induced by the NLRP3 secondary signal activators can lead to the release of oxidized mtDNA into the cytosol, and then NLRP3 inflammasome is activated by the bondage of mtDNA [53].…”
Section: The Role Of Nlrp3 In Inflammationmentioning
confidence: 99%
“…The proper function of mitochondria is also crucial for NLRP3 inflammasome activation. Several factors including NO [51] and Ca 2+ [52] can lead to MtD, which may also trigger the NLRP3 inflammasome activation via the release of oxidized mitochondrial DNA (mtDNA) following the engagement of TLRs [21]. MtD induced by the NLRP3 secondary signal activators can lead to the release of oxidized mtDNA into the cytosol, and then NLRP3 inflammasome is activated by the bondage of mtDNA [53].…”
Section: The Role Of Nlrp3 In Inflammationmentioning
confidence: 99%
“…In this regard, the gas messenger nitric oxide (NO) has been reported to regulate mitochondrial function by binding to cytochrome c oxidase [ 21 , 22 ]. Thus, at low oxygen concentrations, low levels of NO allow cells to become dependent on glycolysis [ 23 , 24 , 25 ]. In addition, we previously reported that low concentrations of the chemical NO donor DETA-NO induce the expression of pluripotency genes Oct4, Nanog and Sox2 and prevent the expression of differentiation genes Gata-4, Gata-6, Brachyury, Fgf5 and Fgf8 in both mouse and human embryonic SCs [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased generation of superoxide anion by the placenta leads to increased peroxynitrite production, resulting in further oxidative stress and endothelial dysfunction in PE patients [8]. Additionally, it has been well established that NO disrupts the mitochondrial respiratory chain in a dose dependent manner, causing changes in the mitochondrial Ca 2+ flux that induce ER Stress in pluripotent stem cells [12]. Taking all of these evidences into account, it is plausible to assume that OS developed in the placenta by the exaggerated generation of ROS would trigger ER stress in the organ, which in turn will increase the apoptosis of the ST.…”
Section: Oxidative Stressmentioning
confidence: 99%